Effects of core training on dynamic balance stability: A systematic review and meta-analysis. Issue 16 (18th August 2022) - Barrio, Ekaitz Dudagoitia; Ramirez-Campillo, Rodrigo; Garcia de Alcaraz Serrano, Antonio; RaquelHernandez-García, Raquel
ABSTRACT: Core stability has a strong relationship with dynamic balance stability (DBS). The purpose of this review with meta-analysis was to analyse the effects of core training programmes from different studies on DBS. A literature search was performed using different databases. Subgroups analyses on duration, training frequency, total sessions, chronological age, training status, equipment and movements were performed. A random-effects model for meta-analyses was used. Thirteen studies were selected for the systematic review and 10 for the meta-analysis, comprising 226 participants. A moderate effect was noted for core training on DBS (p < 0.001; ES = 0.634). Greater DBS improvements were found in core training interventions with ≤6 weeks (ES = 0.714), after high volume (ES = 0.787) and more frequent interventions (ES = 0.787), as well as in younger participants (ES = 0.832). In addition, body weight exercises may be better than med ball, swiss ball or band resisted exercises. Core training improves DBS among athletes and a non-trained population, creating a more solid stable base that allows better lower extremity movements. This could be more effective considering different modulators ≤6 weeks intervention, >2 sessions per week, >17 total sessions, body weight core programmes and applied to ≤18.0 years old.